Practical Application of Nanotechnology Solutions in Pavement Engineering: Identifying, Resolving and Preventing the Cause and Mechanism of Observed Distress Encountered in Practice during Construction Using Marginal Materials Stabilised with New-Age (Nano) Modified Emulsions (NME) - Gerrit J. Jordaan; Wynand J. vdM. Steyn (Applied Sciences, 2022)
New-age (Nano) Modified Emulsions (NME) for stabilising marginal materials used in the upper-pavement layers of roads have been proven in laboratories, through accelerated pavement tests (APT) in the field as well as in practice. In addition, materials design methods have been developed based on the scientific analysis of granular material mineralogy and the chemical interaction with the binder to design a material-compatible anionic NME stabilising agent for naturally available (often marginal) materials. However, any new disruptive technology that is introduced into a traditionally well-established industry, such as the road construction industry, is usually associated with considerable resistance. This is especially relevant when the new technology enables the use of granular materials traditionally considered to be of an unacceptable quality in combination with relatively new concepts such as an anionic NME stabilising agent. In practice, few road construction projects are without problems. New technologies are obviously easy targets to blame for any non-related problems that may arise during construction. In this article, we aim to assist in pre-empting, recognising, preventing, and resolving material or non-material related construction problems by correctly identifying the cause of the problems and recommending the best, most cost-effective ways to correct any deficiencies on site.